2011
DOI: 10.4070/kcj.2011.41.7.394
|View full text |Cite
|
Sign up to set email alerts
|

Associated Symptoms of Kawasaki Disease

Abstract: Background and ObjectivesIn addition to diagnostic criteria, a broad range of nonspecific clinical features can be found in patients with Kawasaki disease. This lack of specificity may cause confusion with other febrile illnesses and delay the diagnosis of Kawasaki disease. The purpose of this study is to describe common associated symptoms and their clinical significances in children affected with Kawasaki disease.Subjects and MethodsAs a retrospective study, we reviewed the medical records of 121 children wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 15 publications
(16 reference statements)
6
18
1
1
Order By: Relevance
“…In our study, we found the following “nonclassical” symptoms of KD: cough, abdominal pain, vomiting, diarrhea, and arthralgia, which is similar to what was reported in the previous studies [14, 19]. …”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found the following “nonclassical” symptoms of KD: cough, abdominal pain, vomiting, diarrhea, and arthralgia, which is similar to what was reported in the previous studies [14, 19]. …”
Section: Discussionsupporting
confidence: 91%
“…In the study, incomplete KD was defined as the presence of ≤4 principal symptoms defined according to the Japanese diagnostic criteria1) (corresponding to ≤3 principal features of the AHA diagnostic criteria2)) regardless of whether the patient had coronary artery abnormalities; their incomplete presentation group included 271 children (1.2%) with only one or 2 principal symptoms 14). Currently, a diagnosis of incomplete KD might be performed in cases with fewer classical diagnostic criteria and several compatible clinical, laboratory, or echocardiographic findings, based on the exclusion of another febrile illness 15). The above-mentioned results of the survey by Sudo et al14) seem to reflect the current diagnosing practice for incomplete KD.…”
Section: Discussionmentioning
confidence: 99%
“…This distribution of clinical signs was reported that in the previous studies. 16,21 In our study as well, these changes were also less commonly observed in incomplete KD. In the present study gastrointestinal symptoms, sterile pyuria and arthralgia were found as non-classical signs which are consistent with the findings of Yun et al and Manlhiot et al who demonstrated abdominal pain, vomiting, diarrhea, and Majority of the children had raised WBC (75%), raised ESR (95%), increased platelet count (70%) and elevated CRP (75%).…”
Section: Discussionmentioning
confidence: 50%